Strategi ketidaksantunan bahasa dalam komen Malaysiakini / Murugan Krishnan - Murugan , Krishnan (2018)
Malaysiakini social website is one of the most popular electronic media on Facebook. About 1.8 million Facebook users follow the Malaysiakini social website. The use of computer-based communication or computer-mediated communication (CMC), especially Facebook, is increasingly significant in today's society. Economic, social and political are often a key aspect in a communication in social media, especially through CMC nowadays than in the 80s. These three aspects play an important role in people's daily life. Increased communication in any aspect or issue, especially the issue of rising petrol prices that are always closely linked to the people's daily lives has also contributed to the development of impoliteness among Facebook users. The issue of rising petrol prices in Malaysia on the Malaysiakini social website (Malay Version) has received high reaction and response from Facebook users who are Malaysians. Malaysiakini (BM) has given Facebook users the opportunity to give their views and responses to the increase in petrol prices without any restrictions. The Government of Malaysia is a party with full responsibility for this issue. Indirectly Malaysiakini social website (BM) has become one of the fields of communication between the people and the Government. Therefore, researcher want to investigate the types of impoliteness strategies used by Facebook users in the Malaysiakini (BM) social commentary. Culpeper’s Impoliteness Strategy (1996; 2005) has been used for the first research question. While for the second question, researcher have used the Culpeper’s Impoliteness Strategy (2011) to analyze the elements of impoliteness in comments on petrol prices. A total of 60 comments were selected from 2016 and 2017 as the study data for this study. The findings show the strategy of Bald on Record impoliteness strategy and sarcasm strategy are widely used by Facebook users in the Malaysiakini (BM) social commentary on the issue of rising petrol prices. In addition, a combination of impoliteness strategies also obtained in this study. Among them, the combination of Bald on record impoliteness strategies and Sarcasm widely used in Malaysiakini (BM) social commentary. On the second question, the results show that the use of pronoun and sarcastic statements or sarcasm is used by Facebook users in comments on the issue of rising petrol prices. In conclusion, Facebook users on the Malaysiakini social website (BM) are more open in expressing their feelings to the Government, YAB Prime Minister and Malaysians without any restrictions. The increase in petrol prices by the Malaysian Government has sparked people's dissatisfaction to form impoliteness language in Malaysiakini's (BM) social commentary. In short, changes in the economic aspects have caused the people to react to the country's politics.